Neuroprotective Effects of Selected Microbial-Derived Phenolic Metabolites and Aroma Compounds from Wine in Human SH-SY5Y Neuroblastoma Cells and Their Putative Mechanisms of Action - Esteban-Fernández, A.; Rendeiro, C.; Spencer, J. P. E.; del Coso, D. Gigorro; de Llano, M. D. González; Bartolomé, B.; Moreno-Arribas, M. V. (Frontiers in Nutrition, 2017)
Moderate wine consumption has shown the potential to delay the onset of neurodegenerative diseases. This study investigates the molecular mechanisms underlying the protective effects of wine-derived phenolic and aroma compounds in a neuroinflammation model based on SIN-1 stress-induced injury in SH-SY5Y neuroblastoma cells. Cell pre-treatment with microbial metabolites found in blood after wine consumption,3,4-dihydroxyphenylacetic (3,4DHPA), 3-hydroxyphenylacetic (3HPA) acids and salicylic β-D-O-glucuronide, at physiologically concentrations (0.1-10 μM) resulted in increased cell viability versus SIN-1 control group (p <0.05) . Results also showed significant decreases in MAPK p38 and ERK1/2 activation and in downstream proapoptotic caspase-3 activity by some of the studied compounds. Moreover, p38, MEK and ERK1/2 specific inhibitors which have a phenolic-like structure, also resulted in an increase on cell survival and a reduction on caspase-3 activity levels. Overall, these results contribute with new evidences related to the neuroprotective actions of wine, pointing out that wine-derived human metabolites and aroma compounds may be effective at protecting neuroblastoma cells from nitrosative stress injury by inhibiting neuronal MAPK p38 and ERK1/2 as well as downstream caspase 3 activity.